Characterization of the appendicular skeleton of Saimiri sciureus - Blanco Rodríguez, Julio César (2015)
The bones of the anterior and posterior limbs of the primate Saimiri sciureus are described. Five dead specimens that were seized and kept under medical observation at the «Hogar de Paso para Fauna Silvestre», Caquetá, Colombia were used for the study. Detailed description of each bone is presented, including the average measures.